2021
DOI: 10.1186/s13034-021-00365-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing adverse childhood experiences, social, emotional, and behavioral symptoms, and subjective health complaints among Hungarian adolescents

Abstract: Background Adverse Childhood Experiences (ACEs) can have lifelong adverse impacts; they can play a role in the development of subsequent emotional, cognitive, and social impairments leading to somatic and mental difficulties, as well as health damaging behaviours. Unfortunately, there are currently no research data available in Hungary regarding the frequency of ACEs among adolescents. Aims A cross sectional questionnaire survey was conducted in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 50 publications
3
11
0
7
Order By: Relevance
“…A relationship between female gender and increased exposure to adverse childhood experiences was a subject of numerous studies. Similar conclusions were obtained by Andrés F. Sciolla et al whose research concerned 86 medical students of one medical school on the West Coast of the USA and Beáta Kovács-Tóth et al studying a population of 516 Hungarian teenagers aged 12-17 [10,14].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A relationship between female gender and increased exposure to adverse childhood experiences was a subject of numerous studies. Similar conclusions were obtained by Andrés F. Sciolla et al whose research concerned 86 medical students of one medical school on the West Coast of the USA and Beáta Kovács-Tóth et al studying a population of 516 Hungarian teenagers aged 12-17 [10,14].…”
Section: Discussionsupporting
confidence: 81%
“…Our study showed that women had a statistically significant higher chance than men of experiencing psychological abuse, sexual abuse and emotional neglect. The available literature provides similar conclusions [10,14,15]. Moreover, the research conducted by Andrés F. Sciolla et al showed a correlation between female gender and higher exposure to physical abuse [10].…”
Section: Discussionmentioning
confidence: 59%
“…10 All sorts of physical, emotional, or sexual negative and traumatic experiences occurring in the family before the age of 18 years such as domestic violence, divorce, and separation give rise to adverse childhood experiences (ACEs). 17 The major reasons are economic challenges, family conflicts, parents with alcohol or drug addiction, negative family circumstances, and parents' divorce or loss. 18 Considering that almost one in every two adults has an adverse childhood experience, this situation has an unignorable dimension.…”
Section: Introductionmentioning
confidence: 99%
“…18 Considering that almost one in every two adults has an adverse childhood experience, this situation has an unignorable dimension. 17 Parents' divorce or separation was reported as the second most common ACE. 19 Divorce rate had significant growth in several countries in the past five decades.…”
Section: Introductionmentioning
confidence: 99%
“…They are also associated with negative behavioral outcomes such as increased health care utilization (Alcalá et al, 2018), earlier age at sexual debut (Brown, Masho, et al, 2015), HIV risk behavior (Fang et al, 2016; VanderEnde et al, 2018), and intimate partner violence victimization (Thulin et al, 2021) and perpetration (Brown, Masho, et al, 2015). In addition, ACEs have been positively associated with subjective health complaints (Kovács-Tóth et al, 2021) and negatively associated with subjective well-being (Kelifa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%